Clinical validity and intrarater and test–retest reliability of the Structured Clinical Interview for DSM‐5 – Clinician Version (SCID‐5‐CV) - Osório, Flávia L.; Loureiro, Sonia Regina; Hallak, Jaime Eduardo C.; Machado‐de‐Sousa, João Paulo; Ushirohira, Juliana M.; Baes, Cristiane V. W.; Apolinario, Thiago D.; Donadon, Mariana F.; Bolsoni, Livia M.; Guimarães, Thiago; Fracon, Victor S.; Silva‐Rodrigues, Ana Paula Casagrande; et al. (Psychiatry and clinical neurosciences, 2019)
Aim The Structured Clinical Interview for the DSM is one of the most used diagnostic instruments in clinical research worldwide. The current Clinician Version of the instrument (SCID‐5‐CV) has not yet been assessed in respect to its psychometric qualities. We aimed to assess the clinical validity and different reliability indicators (interrater test–retest, joint interview, face‐to‐face vs telephone application) of the SCID‐5‐CV in a large sample of 180 non‐prototypical and psychiatric patients based on interviews conducted by raters with different levels of clinical experience. Methods The SCID‐5‐CV was administered face‐to‐face and by telephone by 12 psychiatrists/psychologists who took turns as raters and observers. Clinical diagnoses were established according to DSM‐5 criteria and the longitudinal, expert, all data (LEAD) procedure. We calculated the percentage of agreement, diagnostic sensitivity and specificity, and the level of agreement (kappa) for diagnostic categories and specific diagnoses. Results The percentage of positive agreement between the interview and clinical diagnoses ranged between 73% and 97% and the diagnostic sensitivity/specificity were >0.70. In the joint interview, the levels of positive agreement were high (>75%) and kappa levels were >0.70 for most diagnoses. The values were less expressive, but still adequate, for interrater test–retest interviews. Conclusion The SCID‐5‐CV presented excellent reliability and high specificity as assessed with different methods. The clinical validity of the instrument was also confirmed, which supports its use in daily clinical practice. We highlight the adequacy of the instrument to be used via telephone and the need for careful use by professionals with little experience in psychiatric clinical practice.